Crop yield and weed growth under conservation agriculture in semi-arid Zimbabwe - Mashingaidze, Nester; Madakadze, Casper; Twomlow, Stephen; Nyamangara, Justice; Hove, Lewis (Soil & tillage research, 2012)
► Studied effect of tillage, mulch and weeding on weed growth in cowpea and sorghum. ► High early season weed growth was observed in minimum tillage (MT) systems. ► Maize mulching associated with high mid- to late-season weed growth in both crops. ► Frequent hoe weeding decreased weed growth and improved crop yields. ► Crop grain yields poorer in MT systems than in conventional mouldboard plough. Constraints to effective weed management may be the main reason for the small area under minimum tillage (MT) in smallholder farming in southern Africa. The effect of maize residue mulching and intensity of hand hoe weeding on the growth of weeds, cowpea (Vigna unguiculata cv. IT 86D-719) and sorghum (Sorghum bicolor cv. Macia) was investigated in the fifth and sixth years of a conservation agriculture (CA) field experiment at Matopos Research Station (28°30.92′E, 20°23.32′S). The experiment was a split-plot randomized complete block design with three replications. Tillage was the main plot factor (conventional tillage – mouldboard plough compared against MT systems – ripper tine and planting basins) and maize residue mulch rate (0, 4 and 8tha−1) the sub-plot factor. Hoe weeding was done either four times (high weeding intensity) or twice (low weeding intensity) during the cropping season. Planting and weeding were done at the same time in all treatments. There was markedly greater early season weed growth in MT systems relative to mouldboard plough (MBP) in both crop species. In sorghum, MT (planting basins: 40.3kgha−1; ripper tine: 34.8kgha−1) systems had higher cumulative weed biomass measured after planting than MBP (29.9kgha−1) system. Maize mulching was generally associated with increased mid- to late-season weed growth in the two crops probably due to improved soil moisture conservation during periods of low precipitation. Weed suppression by the maize mulch was observed only in sorghum and limited to early in the cropping season with no effect observed for the remainder of the sorghum rotation phase. The high weeding intensity treatment had lower weed growth in both crops and better sorghum yield than low weeding intensity. The MT systems had poor crop establishment which translated into low yields. Cowpea grain yield obtained from MT systems was less than 300kgha−1 compared to 413kgha−1 in MBP. The poor sorghum establishment in MT systems translated into low grain yield as sorghum grain yield was lowest in planting basins (2602kgha−1) and highest in MBP with 4159kgha−1. Results suggest that CA systems require early and frequent hoe weeding even after four years to reduce weed infestations and improve crop growth. This higher demand on a smallholder household's limited labor supply throughout the cropping season will be a key determinant of the spread and adoption of CA in southern Africa.